2
$\begingroup$

From the elements of statistical learning, it was claimed that $$ \frac{1}{N}\sum_{i=1}^N ||h(x_i) ||^2 \sigma^2_\varepsilon= \frac{p}{N}\sigma^2_\varepsilon$$

where $h(x_i) = X(X^TX)^{-1}x_i$. Can someone show me how to prove this ? Thanks

This came from the image below

enter image description here

$\endgroup$

1 Answer 1

2
$\begingroup$

$$ \sum_{i=1}^{N}\|\textbf{h}(x_i)\|^2 =\sum_{i=1}^{N}\|\textbf{X}(\textbf{X}^T\textbf{X})^{-1}x_i\|^2 =tr\{(\textbf{X}(\textbf{X}^T\textbf{X})^{-1}\textbf{X}^T)^T(\textbf{X}(\textbf{X}^T\textbf{X})^{-1}\textbf{X}^T)\} =tr\{(\textbf{X}(\textbf{X}^T\textbf{X})^{-1}\textbf{X}^T)(\textbf{X}(\textbf{X}^T\textbf{X})^{-1}\textbf{X}^T)\} =tr\{\textbf{X}(\textbf{X}^T\textbf{X})^{-1}(\textbf{X}^T\textbf{X})(\textbf{X}^T\textbf{X})^{-1}\textbf{X}^T\} =tr\{\textbf{X}(\textbf{X}^T\textbf{X})^{-1}\textbf{X}^T\} =tr\{\textbf{X}^T\textbf{X}(\textbf{X}^T\textbf{X})^{-1}\} =tr\{\textbf{I}_p\}=p $$ Q.E.D.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.